(untitled) (World Bulletin of Public Health, 2025)
IgA vasculitis (previously known as Henoch-Schönlein purpura) is a smallvessel vasculitis characterized by immune complex deposition, predominantly affecting children. While most cases resolve spontaneously, a significant minority may develop recurrent, severe forms of the disease, especially when kidney function is compromised. We present an 11-year-old boy with recurrent, systemic IgA vasculitis manifesting with nephrotic-range proteinuria, gastrointestinal symptoms, and persistent skin purpura. This case highlights the diagnostic complexity, pathophysiological underpinnings, and therapeutic considerations in managing refractory IgA vasculitis in pediatric patients.